Islamic Parenting and Motivation from Parents and Its Influence on Children's Ability to Read the Quran - Elvina, Elvina; Ritonga, Mahyudin; Lahmi, Ahmad (Universitas Muhammadiyah Magelang, 2021)
The motivation of learners to learn the Qur'an in this day and age is very low, learners at the time to learn the Qur'an choose television activities, play games and others, therefore motivation from parents is needed to minimize the activities of learners who are less useful. Previous studies show that external factors affect Islamic children's development and ability to read the Quran. Therefore, this study aimed to determine how parenting techniques and motivation influence children's ability to read the Quran. A quantitative approach with a sample population of 100 persons was used, while data was collected through questionnaires and examining the existing documents. The results showed that 1) Islamic parenting has a 78% contribution to the children's ability to read the Quran, 2) the motivation by parents affect the children's ability by 1.5%, 3) the combination of parent motivation and parenting techniques accounts for 79.5% of the effect, and 4) parenting style and motivation from parents simultaneously influence children's ability. Based on the description of existing data it can be concluded that parents have a fundamental role in providing motivation for learners to learn the Qur'an.